Bioacumulation of cadmium (Cd) Within water around the final solid waste disposal (FWD) of Sukawinatan Palembang - Deni Julius; Suheyanto Suheryanto; Laila Hanum (Research Centre of Inorganic Materials and Complexs, 2018)
There has been research on the Bioacumulation of Cadmium in the Leachate, Sediment, Sepat fish and watercress within water around the final solid waste disposal (FWD) of Sukawinatan Palembang using Atomic Absorption Spectrophotometric (SSA) technique. This study aims to determine the distribution of cadmium contained in water ecosystem within water around the final solid waste disposal (FWD) of Sukawinatan, as well as bioconcentration factor (BCF) of the biotic compartement to the abiotic compartement . The way is done by wetdestruction sample. The resultant destruction solution was analyzed at a wavelength of 228.8 nm. The results showed that the concentration of cadmium in leachate Inlet 0,0099 mg/L until the Sedapat River 0,0010 mg/L, Sediment Inlet 0,0427 mg/Kg until Sedapat River Sediment 0,0051 mg/Kg, Sepat fish reservoir 0,0099 mg/Kg and Sepat fish Sedapat River 0,0096 mg/Kg along watercress reservoir 0,0042 mg/Kg over Sedapar river 0,0027 mg/Kg. So that distribution of cadmium for water and sediment compartment getting further from leachate inlet to Sedapat river is decreasing. The value of cadmium consentration in leachate is still below the threshold conformable in regulation of environment and forestry ministers no.59 of 2016 is 0,1 mg/L. Distribution on the fish and watercress compartment also descreased to the Sedapat river. Consentration value on the fish and watercress also stil below the quality standard in this SNI 7378;2009 for fish 0,1 mg/Kg and watercress 0,2 mg/Kg. While the value of BCF fish and BCF watercress <100 is still in low category.